Productivity of Red Clover (Trifolium pratense L.) in Various Ways of Use in Soil and Climatic Conditions of the Western Region of Ukraine - Lesia Baystruk-Hlodan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Red clover (Trifolium pratense L.) is a perennial plant of the legume family (Fabaceae). It is grown both in pure culture and in crops with perennial grasses. This study aims to assess the yield of red clover for hay (two cuttings) and pasture (four slopes) use in the soil and climatic conditions of the Western region of Ukraine. The subject of the study is four breeding numbers created by hybridization and selection methods. The placement of variants is systematic in a sequential arrangement of repetitions in several tiers. Field experiments were carried out over three years (2018–2020) in competitive variety testing. The study found that, on average, the period from regrowth to slope ripeness lasted 67–95 days, from regrowth to pasture ripeness (30–61 days), and from regrowth to economic ripeness of seeds (136–172 days), depending on the years of cultivation. With the hay use of red clover, the yield is 41.14–44.78 t/ha, with the pasture 50.18–52.38 t/ha.